Exploring nagZ as a virulence biomarker and treatment target in Enterobacter cloacae - Xianggui Yang; Xuejing Yu; Li Zhou; Dan Wang; Weixian Chen (BMC Microbiology)
Abstract Background Enterobacter cloacae is increasingly prevalent and resistant to multiple antibiotics, making it a significant pathogen in healthcare settings with high mortality rates. However, its pathogenic mechanisms are not fully understood. Results In this study, we explored the role of nagZ in regulating the virulence of E. cloacae and its potential as a therapeutic target. Our research showed that pathogenic strains of E. cloacae express higher levels of nagZ than colonizing strains, particularly in simulated infection environments. Deleting nagZ significantly reduced E. cloacae virulence in various infection models, including Galleria mellonella larvae, mice, and RAW264.7 cells. Moreover, nagZ knockout decreased the bacterium's ability to induce inflammatory factor levels, while complementing nagZ in knockout strains partially rescued this ability. Importantly, the absence of nagZ also enhanced the antibacterial efficacy of ceftazidime against E. cloacae. Conclusions These findings underscore the crucial role of nagZ in E. cloacae pathogenesis and highlight its potential as a novel therapeutic target for treating infections caused by this pathogen.